Flammability properties of intumescent vinyl acetate–ethylene copolymer emulsion including natural carbonization agent. (6th April 2022) - Lu, Jinhan; Li, Luming; Jiang, Peng; Chen, Zhilin; Fontaine, Gaëlle; Zhang, Yahui; Yu, Guoping; Bourbigot, Serge
Abstract: Melamine amino trimethyl phosphate (M-AT) has been mixed with bio-based starch, chitosan, or sodium lignosulfonate (SL), and used to prepare an intumescent flame retardant (IFR) vinyl acetate-ethylene copolymer emulsion (VAE), which might be used for the formulation of adhesives, coatings, etc . The goal was to meet the performance requirements especially with respect to flame retardance and mechanical properties. The flammability of VAE adhesives was assessed using limiting oxygen index (LOI), UL-94 vertical burning, and cone calorimetry tests (CCT). The presence of 30 wt% of the M-AT/SL compounds (mass ratio of M-AT to SL was 3:1) in VAE polymer brought a 73% reduction in peak of heat release rate (139.2–37.1 kW/m 2 ) in CCT. The LOI was increased to 31.5 from 20, the UL94 grade was upgraded to V-0 (sample thickness: 5 mm). The formation of bubble-shaped char layer can be promoted by polyphosphoric acid and benzenesulfonic acid along with ammonia and sulfur dioxide, which generated by the thermal decomposition of synthesized M-AT and SL during combustion of the polymer. In addition, the incorporation of 30 wt% M-AT/SL compounds in VAE matrix leaded to a 56% and 40% increasement in tensile strength and elongation at break tests, respectively compared to the pure one. This work offers a green and novel method for the production of high-performance VAE adhesives with fire resistance properties. Graphical abstract: Image 1 Highlights: A novel intumescent flame retardant system for VAE polymer proposed. Intumescent VAE polymer with excellent flame retardance, thermal stability, and mechanical properties. Evolution of intumescent char layer investigated. Mechanism of flame-retardance investigated.